Factors Affecting Customer Retention at Authorised Commercial Vehicle Workshops in India - David, Joiestin (Digital Repository of Theses, 2025)
Retaining customers is vital for any business. Acquiring a new customer is very expensive while retaining customers help in growing the business further. Lot of research have been already carried out in the domain of customer retention across industries. Commercial Vehicle Business in India is one of the critical components in the economic activity of the country. It is cyclical in nature. The life of these vehicles is more than 15 years. To make such long durable products perform efficiently, a strong after-sales service is required. The number of registered commercial vehicles on the roads of the country are increasing every year, which is in turn attracting many new workshops to come up. The Commercial Vehicle (CV) manufacturers are investing heavily in the expansion of their sales and service network to cater to this growing population. Very little research has been carried out in the past with respect to customer retention at authorised workshops. Retaining customer is essential for a CV manufacturer to get vehicle performance feedback as well as to ensure that their channel partners’ business is viable. It is observed that the customers move away from authorised workshops as the vehicles get older. This research has been able to shortlist the factors which affects customers’ visit to a workshop for availing its services. The list of 38 factors which affect customer retention based on extensive literature review was obtained. Through experts’ scoring and evaluation, a list of 20 factors was shortlisted. These 20 factors were subjected to pairwise comparison by industry experts using Analytic Hierarchy Process (AHP) as well as Decision Making Trial & Evaluation Laboratory (DEMATEL) method. The AHP study was used to obtain the relative weights of these factors and DEMATEL method was used to obtain the relationship between these factors. The insights from the combined study helped in identifying 9 factors which are relatively important. Strategies as well as practically implementable ideas have been suggested based on these 9 factors for the CV manufacturers, which could probably help them retain the customers at their authorised workshops.